A TRiP RNAi screen to identify molecules necessary for Drosophila photoreceptor differentiation. - Rylee, J.; Mahato, S.; Aldrich, J.; Bergh, E.; Sizemore, B.; Feder, L.E.; Grega, S.; Helms, K.; Maar, M.; Britt, S.G.; Zelhof, A.C. (G3 : genes - genomes - genetics, 2022)
Drosophila rhabdomeric terminal photoreceptor differentiation is an extended process taking several days to complete. Following ommatidial patterning by the morphogenetic furrow, photoreceptors are sequentially recruited and specified, and terminal differentiation begins. Key events of terminal differentiation include the establishment of apical and basolateral domains, rhabdomere and stalk formation, inter-rhabdomeral space formation, and expression of phototransduction machinery. While many key regulators of these processes have been identified, the complete network of transcription factors to downstream effector molecules necessary for regulating each of these major events remains incomplete. Here, we report an RNAi screen to identify additional molecules and cellular pathways required for photoreceptor terminal differentiation. First, we tested several eye-specific GAL4 drivers for correct spatial and temporal specificity and identified Pph13-GAL4 as the most appropriate GAL4 line for our screen. We screened lines available through the Transgenic RNAi Project and isolated lines that when combined with Pph13-GAL4 resulted in the loss of the deep pseudopupil, as a readout for abnormal differentiation. In the end, we screened 6,189 lines, representing 3,971 genes, and have identified 64 genes, illuminating potential new regulatory molecules and cellular pathways for the differentiation and organization of Drosophila rhabdomeric photoreceptors.